Neratinib and metformin: A novel therapeutic approach against HER2-Positive Breast Cancer - Kheraldine, Hadeel (2025)
BackgroundHER2-positive breast cancer (BC) is highly aggressive with a poor prognosis. It is driven by HER2 oncoprotein activation/crosstalk with other receptors like EGFR/(HER1), HER3, and HER4, in addition to IGF-1R, making these receptors ideal therapeutic targets as they are expressed/overexpressed in this subtype. We postulated that targeting HER2 and IGF-1R together is a promising therapy for HER2-positive BC. Thus, we explored the outcome of a novel combination treatment using neratinib, a pan-HER inhibitor, and metformin, an IGF-1R inhibitor, on HER2-positive BC cells. Methods: In this investigation, we used cellular and molecular biology techniques in addition to an angiogenesis model and tissue microarray analysis. Results: Our data revealed that this combination therapy significantly reduced cell viability compared to individual treatments and exhibited a synergistic effect in HER2-positive BC cells. Moreover, the combination disrupted cell cycle progression and inhibited colony formation, and invasion of HER2-positive BC cells; this is accompanied by the deregulation of HER1–3 and IGF-1R expression patterns, in addition to Caspase-3, BCL2, Fascin, and Vimentin. Moreover, key regulator molecular pathways, including, ERK1/2, AKT, p38 MAPK, and mTOR, were significantly downregulated upon treatment with neratinib and metformin combination. Additionally, our data pointed out that neratinib and metformin combination inhibited angiogenesis, in-ovo, an important biological event in cancer progression. Finally, using a cohort of 55 HER2-positive BC samples, we revealed that HER2 and IGF-1R are co-expressed in most of the cases. Conclusions: These findings suggest that neratinib and metformin combination can present a promising strategy for targeting multiple pathways in HER2-positive BC.